Effects of mindfulness-based programs on competitive anxiety in sports: a meta-analysis - Wang, Xiaolin; Mohd Nasiruddin, Nasnoor Juzaily; Ji, Shuyu; Gao, Xuejiao; Hassan, Muhammad Zarif; Dong, Delong; Samsudin, Shamsulariffin (Springer, 2024)
This review aimed to investigate the effects of mindfulness-based programs (MBP) on competitive anxiety among athletes. SPORTDiscus, CNKI, Web of Science, PubMed, and ProQuest databases were searched for relevant studies published by July 2023. R packages were used for this meta-analysis. The Physiotherapy Evidence Database (PEDro) was applied to assess the methodological study quality. A total of 20 articles were included in this meta-analysis. Meta-results showed a medium-to-large effect of the MBP in reducing athletes’ competitive anxiety (g = -0.67, 95% CI [-0.92, -0.42]). The subgroup analyses revealed that the effectiveness of the MBP on competitive anxiety was robust regardless of MBP type, sport, age, and gender. However, the MBP effectiveness might be more prominent for non-Western athletes compared to Western athletes, and for high-level athletes (e.g., regional or national) compared to low-level athletes (e.g., local or university), as well as when interventions lasted more than 7 weeks. Additionally, separate meta-analyses revealed moderate-to-large effects in terms of cognitive anxiety (g = -0.76, 95% CI [-1.32, -0.19]) and somatic anxiety (g = -0.84, 95% CI [-1.26, -0.42]), as well as a small to moderate effect for self-confidence (g = 0.45, 95% CI [0.15, 0.75]).In conclusion, the MBP consistently and effectively reduces competitive anxiety levels among athletes. In the future, high-quality, adequately powered studies are needed to further explore the effects of MBP on the internal dimensions of competitive anxiety and understand the impact of various factors (e.g., MBP type, competitive level and country) on MBP effectiveness.